Magnitude and patterns of severe Plasmodium vivax monoinfection in Vietnam: a 4-year single-center retrospective study - Duong, Minh Cuong; Pham, Oanh Kieu Nguyet; Thai, Thanh Truc; Lee, Rogan; Nguyen, Thanh Phong; Nguyen, Van Vinh Chau; Nguyen, Hoan Phu (Frontiers in Medicine, 2023)
Infection with Plasmodium vivax is a recognized cause of severe malaria including deaths. The exact burden and patterns of severe P. vivax monoinfections is however still not well quantified, especially in P. vivax endemic regions. We examined the magnitude and patterns of severe malaria caused by monoinfections of P. vivax and associated predictors among patients admitted to a tertiary care center for malaria in Vietnam. A retrospective cohort study was conducted based on the patients’ medical records at the Hospital for Tropical Diseases from January 2015 to December 2018. Extracted information included demographic, epidemiologic, clinical, laboratory and treatment characteristics. Monoinfections with P. vivax were found in 153 (34.5%, 95% CI 30.3-39.1%) patients of whom, uncomplicated and severe malaria were documented in 89.5% (137/153, 95% CI 83.7–93.5%) and 10.5% (16/153, 95% CI 6.5–16.3%), respectively. Patterns of severe malaria included jaundice (8 cases), hypoglycemia (3 cases), shock (2 cases), anemia (2 cases), and cerebral malaria (1 case). Among 153 patients, 73 (47.7%) had classic malaria paroxysm, 57 (37.3%) had >7 days of illness at the time of admission, and 40 (26.1%) were referred from other hospitals. A misdiagnosis as having other diseases from malaria cases coming from other hospitals was up to 32.5% (13/40). Being admitted to hospital after day 7th of illness (AOR = 6.33, 95% CI 1.14–35.30, P = 0.035) was a predictor of severe malaria. Severe malaria was statistically associated with longer hospital length of stay (P=0.035). Early and late treatment failures and recrudescence were not recorded. All patients recovered completely. This study confirms the emergence of severe vivax malaria in Vietnam which is associated with delayed hospital admission and increased hospital length of stay. Clinical manifestations of P. vivax infection can be misdiagnosed which results in delayed treatment. To meet the goal of malaria elimination by 2030, it is crucial that the non-tertiary hospitals have the capacity to quickly and correctly diagnose malaria and then provide treatment for malaria including P. vivax infections. More robust studies need to be conducted to fully elucidate the magnitude of severe P. vivax in Vietnam.